Naturalizing Family Values in Disney’s Encanto (2021): A Roland Barthes Semiotic Analysis - Nur Meilani, Risma; Iskandar; Muhammad Rifqi Syamsuddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the representation of family values in Disney's Encanto (2021) by applying Roland Barthes' semiotic theory. The study aims to identify how family values are represented through denotative, connotative, and mythological meanings, particularly the process of naturalization reflected in the film. This research employed a qualitative descriptive method. The data consisted of visual and verbal signs related to family values in the film and were collected through observation and documentation. The data were analyzed using Barthes' semiotic framework, including denotation, connotation, and myth. The findings reveal that the film represents family values through signs of love, responsibility, sacrifice, empathy, forgiveness, acceptance, solidarity, and family unity. At the connotative level, these values are conveyed through characters' facial expressions, gestures, dialogue, settings, and symbolic objects that reflect emotional experiences within the Madrigal family. At the mythological level, the film naturalizes cultural beliefs that family members are expected to support one another, maintain family harmony, and prioritize collective well-being. At the same time, the film challenges the naturalized belief that personal worth depends on perfection or extraordinary abilities by emphasizing that unconditional love, mutual understanding, and acceptance are the true foundations of a strong family. Therefore, Encanto demonstrates that genuine family strength is constructed through emotional connection rather than supernatural power.